2017
DOI: 10.1177/1477153517738306
|View full text |Cite
|
Sign up to set email alerts
|

A whole-year approach showing that ambient light level influences walking and cycling

Abstract: Many studies have used surveys to investigate the reactions to changes in lighting from people who walk or cycle. An alternative approach is to use objective data, specifically the number of pedestrians and cyclists present under different lighting conditions. Such data have been reported previously using a daylight savings transition approach. This paper presents a different method for analysing the effect of ambient light conditions in which data from the whole year are examined, rather than only the two wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 21 publications
1
38
2
2
Order By: Relevance
“…150 Road lighting should aid the detection of pavement obstacles that might otherwise result in a fall, and the associated research has focussed on the ability to detect pavement irregularities such as a raised paving slab. This is important because falls on public footpaths are a significant problem in terms of the number of cases, the severity of the resulting injury and the national cost.…”
Section: Comparing Approachesmentioning
confidence: 99%
“…150 Road lighting should aid the detection of pavement obstacles that might otherwise result in a fall, and the associated research has focussed on the ability to detect pavement irregularities such as a raised paving slab. This is important because falls on public footpaths are a significant problem in terms of the number of cases, the severity of the resulting injury and the national cost.…”
Section: Comparing Approachesmentioning
confidence: 99%
“…With the awareness that category rating evaluations are prone to response bias (Fotios, 2018) validation from alternative methods is required. With the assumption that greater reassurance results in more walking we have counted pedestrian flows to determine the influence of ambient light, finding that for a given time of day (and thus similar purposes of walking) there are greater numbers of pedestrians at higher levels of ambient light (Uttley and Fotios, 2017;Fotios et al, 2019) but this itself requires validation in a wider range of contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting odds ratio quantifies the effect of darkness on cycling rates, with a larger odds ratio indicating a greater reduction in cyclists associated with darkness. Fotios et al (2019) found an odds ratio for cyclists of 1.67, suggesting people were 1.67 times more likely to cycle during daylight than after-dark, after accounting for time of day and seasonal factors.…”
Section: Lighting and The Confidence To Cyclementioning
confidence: 98%
“…Previous research has demonstrated a link between ambient light levels and cycling rates Fotios et al, 2019). These studies used observational count data from the United States to assess the impact of darkness on the number of people cycling.…”
Section: Lighting and The Confidence To Cyclementioning
confidence: 99%
See 1 more Smart Citation